The Penguatan Kelembagaan Koperasi Unit Desa (KUD) Anjasmoro Kecamatan Wonosalam melalui Edukasi Digitalisasi dan Legalitas Usaha untuk Meningkatkan Kesejahteraan Anggota - Purmiyati, Atik; Hidayati, Nur Aini (Universitas Medan Area, 2025)
This community service activity was designed to strengthen the institutional structure of the Anjasmoro Village Cooperative (KUD) located in Wonosalam District, through the optimization of business legality and increasing the capacity of members in the field of digital marketing. The main problems faced are the low ownership of Business Identification Numbers (NIB) and limitations in the use of e-commerce and social media for digital marketing. The methods used were Focus Group Discussions (FGD), education, mentoring, and periodic evaluations. The results of the activity showed a significant increase in the understanding and skills of MSME actors regarding NIB management and the use of digital platforms such as Shopee, WhatsApp Business, and Instagram for online product marketing. In addition, of the 20 participants who took part in training on NIB creation and digital marketing, 80 percent, or 16 people, already had an NIB and understood digital marketing. This activity proves that educational and participatory interventions can drive digital transformation and local economic empowerment. In addition to supporting the achievement of the Sustainable Development Goals (SDGs), this program also strengthens the competitiveness of MSMEs in the digital era. This activity serves as a model for institutional-based empowerment that can be replicated in other regions.